A Portuguese Don Juan: the deconstruction of myths in the novel by Almeida Faria O Conquistador (The Conqueror) - Sequeira, Rosa Maria (2023)
Political and propagandistic purposes are related to myths as a form of legitimiza-tion and collective memory building. In fiction, the figure of Don Juan has great importance in European culture, having given rise to contaminations with historical figures. Hence, it is pertinent to ask why. Almeida Faria’s novel, O Conquistador (first published in 1990 and reedited in 2017) fuses the myth of Don Juan with that of the Hidden One (O Encoberto), important in the Portuguese and English contexts, creating a third space for cultural criticism.